Children With Disruptive Mood Dysregulation Disorder and Psychopathological Risk in Their Mothers: The Function of Global DNA Methylation - Carola, Valeria; Cimino, Silvia; Bussone, Silvia; Cerniglia, Luca; Tambelli, Renata (Frontiers in Psychiatry, 2021)
Epigenetic mechanisms, in particular DNA methylation, have been implicated in the etiopathogenesis of psychopathologies in adulthood. The significance of this mechanism in child psychopathologies, however, is much less recognized. Here, we examined whether global DNA methylation alteration was associated with the presence of disruptive mood dysregulation disorder (DMDD) in children. Moreover, in light of the relevance of the interplay between children and parents for the onset and maintaining of psychopathology during development, we measured the association between psychological symptoms, attachment styles, and global DNA methylation levels in healthy and DMDD mother-child dyads (mothers: N = 126, age = 38.3 + 2.5 years; children: N = 150, age = 8.2 + 0.9 years, gender ratio [f/m] = 72/78). We did not observe any significant differences in global DNA methylation levels in DMDD children when compared with healthy peers, and children’s symptoms did not correlate with variations in this parameter. The mothers showed different levels of psychological symptomatology. Notably, mothers with high psychological symptomatology showed the lowest levels of global DNA methylation. Maternal global DNA methylation levels were associated with maternal hostility, interpersonal sensitivity, psychoticism, and general severity index. Moreover, we found an effect of maternal mental health on the severity of children's symptoms, independently from both maternal and child DNA methylation levels. Despite here DNA methylation does not appear to be involved in the maternal inheritance of vulnerability to depression, this biological link could still arise in later stages of the child's development.